Activism in the International Geography of Books: Small Publishing Houses from Argentina at the 2020 Virtual Frankfurt Book Fair - Riveiro, María; Szpilbarg, Daniela (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
International Book Fairs are vital for the international geography of books and allow the researcher to observe the relations of domination and the defiant practices that shape book production. This article draws on a survey and in‑depth interviews with small publishing houses from Argentina to analyze their participation in the 2020 Virtual Frankfurt Book Fair, and complements this data with an online observation of the fair. While Argentine history is rich with cases of publishers closely related to politics, we pose the question on the forms activism adopts in the twenty‑first century. This analysis engages in current debates on the links between publishing and politics, centers and peripheries, power dynamics, and on how these phenomena shift in the virtual sphere. This participation is theorized as activism practices, i.e. (i) resistance from dominant practices, (ii) an enthusiastic approach to the virtual sphere, and (iii) cooperation and reliance on institutions.